A case study on the improvement of productivity and efficiency of a quality control line for a cutting tool manufacturer / Muhammad Farhan Mohd Suhaimi and Noor Azlina Mohd Salleh - Mohd Suhaimi, Muhammad Farhan; Mohd Salleh, Noor Azlina (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
A case study conducted at a quality control line of a cutting tool manufacturer in Malaysia aimed to improve the line balancing and maximise the productivity. Line Balancing (LB) plays an important role to enhance the productivity and efficiency of a production line. Current situation at the line is considered very critical since the operator exhibits high tendency to skip a few procedures while performing the inspection processes. It is due to the manpower shortfall in the line that overwhelmed the operator to meet an irrelevant required target output from the line. This situation resulted in some customer complaints on the company's product. In order to overcome the problem, observations and time study using the stopwatch technique had been conducted to identify the flaw concerning the workload at the quality control line. Then, from the data obtained, LB is introduced into the quality control line. The data collected are then analysed by using the takt time calculation, Yamazumi Chart and a new layout of the quality control line are designed and proposed. Apart from that, a pre-filled check sheet acts as a Lean Manufacturing (LM) approach named Poka-Yoke is also introduced with regard to eliminate a few wastes existed in the line. As a result, the productivity and efficiency of the quality control line recorded an increment up to 9.73% and 89.94% respectively. With the aid of this study, it is greatly help the company to establish a better monitoring system to thoroughly Muhammad Farhan Mohd Suhaimi & Noor Azlina Mohd Salleh utilise the resources especially in terms of time and manpower needed for the line.